INFORMATION SECURITY AND CYBER SECURITY: A COMPARATIVE LEGAL ASPECT - Sopilko, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The role of information security and cybersecurity in the modern world is very significant. Today we rely more on technology than ever before. As a result, the volume of digital data creation has increased. Today, companies and governments store most of the important information on computers and transfer it over the Internet to other computers. The devices and systems that underlie them have vulnerabilities that, when exploited, threaten the activities of organizations and even entire governments. It is worth noting that data breaches caused by holes in cybersecurity and incomplete information security systems can have devastating consequences for any business. After all, this can ruin the company’s reputation due to the loss of confidence of consumers and partners. Also, the loss of critical data can cost an organization its competitive advantage. In the future, this problem can affect corporate income due to non-compliance with the rules for protecting confidential information. That is why understanding the essence of information and cybersecurity, as well as their sufficient legal regulation, is now a key aspect in the implementation of the activities of any organization. The purpose of the paper is to study the features and essence of cybersecurity and information security and to make their comparative legal analysis. Research methods: the research was carried out using generally recognized methods of scientific knowledge, such as analytical, comparative-legal, systemic, and structural, and others. Results: the concept, essence, characteristics of cybersecurity and information security are studied, the problems of ensuring their functioning are indicated, recommendations are given to overcome such problems by improving the current legislative framework and harmonizing national legislation with international standards. Discussion: the discussion in the article is conducted on the delimitation of the concept of cybersecurity from the concept of information security and the peculiarities of their legal regulation in the leading countries of the world in comparison with our state.